2020
DOI: 10.1038/s41598-020-60534-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Novel life history strategy in a deep sea fish challenges assumptions about reproduction in extreme environments

Abstract: The deep ocean is frequently assumed to be a homogeneous system lacking the same diverse life history strategies found in shallower waters. However, as our methods for exploring the deep ocean improve, common assumptions about dispersal, reproduction and behavior are constantly being challenged. Fishes exhibit the most diverse reproductive strategies among vertebrates. Understanding life history strategies in deep-sea environments is lacking for many species of fishes. Here, we report a novel reproductive stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Singer et al's 2020 3 conclusion of mouth brooding in Parazen was based on a single specimen of 104.3 mm length, which was obtained from a market in Taiwan. As documented in their paper 3 , this specimen has a large egg mass lodged between and extending forward from its pharyngeal jaws and another, smaller egg mass below the gill arches anterior to the basihyal ('tongue' of Singer et al 2020 3 ). The number of eggs was estimated to be around 530 with an average diameter of 0.73 mm.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Singer et al's 2020 3 conclusion of mouth brooding in Parazen was based on a single specimen of 104.3 mm length, which was obtained from a market in Taiwan. As documented in their paper 3 , this specimen has a large egg mass lodged between and extending forward from its pharyngeal jaws and another, smaller egg mass below the gill arches anterior to the basihyal ('tongue' of Singer et al 2020 3 ). The number of eggs was estimated to be around 530 with an average diameter of 0.73 mm.…”
mentioning
confidence: 76%
“…In their discussion, they stated that "There is no way to tell for sure if the eggs in this specimen are Parazen pacificus given that there has not been a formal description of its eggs or larva." It is exactly this sentence that led us to question the conclusion of Singer et al 2020 3 and to look further into the identity of the eggs that the authors found in the mouth of their specimen. Given the potential implications of their discovery, we wonder why the authors chose not to examine the embryos more closely.…”
mentioning
confidence: 89%
“…Teleost fish have different reproductive tactics, for example, migration [ [1] , [2] , [3] ], different types of spawning [ [4] , [5] , [6] ], parental care that occurs in different ways such as the storage of fertilized eggs in the mouth [ [7] , [8] , [9] ], the construction of nests and the maintenance of continuous aeration of the eggs [ [10] , [11] , [12] ]. In females, mature oocytes indicate some reproductive tactics such as the reproductive period [ 13 , 14 ] and type of spawning [ 15 , 16 ], and the animal's fecundity can be estimated [ 5 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%